Convergent evolution of floral shape tied to pollinator shifts in Iochrominae (Solanaceae). (1st March 2018) - Smith, Stacey D.; Kriebel, Ricardo
Abstract: Flower form is one of many floral features thought to be shaped by pollinator‐mediated selection. Although the drivers of variation in flower shape have often been examined in microevolutionary studies, relatively few have tested the relationship between shape evolution and shifts in pollination system across clades. In the present study, we use morphometric approaches to quantify shape variation across the Andean clade Iochrominae and estimate the relationship between changes in shape and shifts in pollination system using phylogenetic comparative methods. We infer multiple shifts from an ancestral state of narrow, tubular flowers toward open, bowl‐shaped, or campanulate flowers as well as one reversal to the tubular form. These transitions in flower shape are significantly correlated with changes in pollination system. Specifically, tubular forms tend to be hummingbird‐pollinated and the open forms tend to be insect‐pollinated, a pattern consistent with experimental work as well as classical floral syndromes. Nonetheless, our study provides one of the few empirical demonstrations of the relationship between flower shape and pollination system at a macroevolutionary scale.